ANALISIS KEBIJAKAN KEPALA SEKOLAH DALAM MELAKSANAKAN PEMBELAJARAN LANGSUNG MENGGUNAKAN METODE HOME VISIT TERJADWAL DI SDN SERANDAKAN KECAMATAN PONTANG – BANTEN - Alda Liga Vela; Sholeh Hidayat; Ratna Sari Dewi (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This research was motivated by the condition that learning during the pandemic required the schools to conduct distance or online learning. Meanwhile, not all schools could carry out online learning because of several problems, so distance or online learning was ineffective. As a result, the principal created a policy to conduct direct learning through the Home Visit method to solve the problems, like the case at SDN Serandakan. This study aimed to describe the effectiveness of the policies established at SDN Serandakan. This research was qualitative research with a descriptive method. The descriptive method sought to reveal the current state of affairs for further analysis and interpretation. The results of this research were that the policies set by the principal were effective. It was supported by the current quality of learning due to the learning assistance in the previous semester, namely direct learning using the Home Visit method.